Gulliver's travels - Swift, Jonathan ([S.l.] : Dover Publications, 1996)
From the preeminent prose satirist in the English language, a great classic recounting the 4 remarkable journeys of ship's surgeon Lemuel Gulliver. For children it remains an enchanting fantasy; for adults, a witty parody of political life in Swift's time and a scathing send-up of manners and morals in 18th-century England.
Unabridged.